ALBUMIN IMPRINTED AGAROSE MATRIX WITH COPPER (II) CHELATED 3-(2-IMIDAZOLIN-1- YL)PROPYL(TRIETHOXYSILANE) MODIFIED SILICA-BASED CORE FOR HUMAN BLOOD PLASMA PURIFICATION - Ratna Wulan, Dyah
Human serum albumin (HSA), a plasma protein, is widely used for clinical therapy, stem cell media and diagnostic tools. In 2020, 1,018 tons of HSA are needed worldwide, growing of 6% from 2020 to 2027. Most of the HSA comes from the purification of human blood plasma.